Planococcus citri (RISSO) (HEMIPTERA: PSEUDOCOCCIDAE): Male/female relationships and influences in the reproductive biology - Santa-Cecília, Lenira Viana Costa; Prado, Ernesto; Pereira, Andressa Barbosa; Souza, Brígida; Sales, Lara (Coffee Science - ISSN 1984-3909, 2017)
The reproduction of the citrus mealybug, Planococcus citri (Hemiptera: Pseudococcidae) has been reported as biparental with facultative parthenogenesis or exclusively biparental. Parthenogenesis may be an attribute of local populations, thus geographic variations could be determinant for the type of reproduction. Therefore, this work aimed to increase our knowledge on the reproduction of P. citri by evaluating the type of reproduction of a Brazilian population of the citrus mealybug collected in coffee trees (Coffea arabica) in south of Minas Gerais state, Brazil. We explored the kind of reproduction, the effect of the temperature on the sexual ratio, the mating capacity of males of 1 or 2 days after emergency and female´s age from 1 to 40 days old, and the number of successful mating of a male. The citrus mealybug from that population presented sexual reproduction exclusively. There was a bias to a higher female proportion at 20°C and 30°C, rearing temperatures considered no optimal for the mealybug development, while at 25°C conduced to a similar proportion of males and females. No mealybug developed at 15°C. The male sexual maturity seems to occur already inside the cocoon where it remains for about 2 days and was able to mate during the first 24 h after emergence. Although short lived, around 2 days after emergence, the male were able to mate up to 21 females. Females between 1 and 40 days were able to mate and reproduce at the same proportion.